A high-strength acrylic sheet and preparation method thereof
By adding ethyl acrylate, graphene oxide and metal chloride to the formula of acrylic sheets and preparing them by casting, the problem of insufficient mechanical properties and high temperature resistance of acrylic sheets is solved, and the improvement of high strength, high temperature resistance and good flame retardant properties is achieved.
Patent Information
- Application Number
- CN202310526790.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-11
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2043-05-11
AI Technical Summary
The existing acrylic sheets have shortcomings in terms of mechanical properties and high temperature resistance, especially in some molding, strength and processing processes, where there are brittleness, open rows and gaps.
By adding ethyl acrylate, graphene oxide and metal chloride to the formula of the acrylic sheet and preparing it by casting, the mechanical properties and high temperature resistance of the acrylic sheet are improved.
The high strength and high temperature resistance of acrylic sheets have been improved, the tensile strength has been increased by at least 30%, the softening point has been increased by at least 25%, and good flame retardant performance.
Smart Images

Figure BDA0004222990540000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of acrylic sheets, and more specifically, to a high-strength acrylic sheet and a preparation method thereof. Background Art
[0002] Acrylic is commonly known as organic glass. In the field of chemistry, it refers to polymethyl methacrylate, abbreviated as PMMA. It is a polymer obtained by polymerization of acrylic acid and lipids. It is an important plastic polymer material that was developed earlier. It has good transparency, chemical stability and weather resistance, is easy to dye, easy to process, has a beautiful appearance, and has excellent comprehensive performance. It is widely used in the construction industry. Organic glass products can usually be divided into cast plates, extruded plates and molded plates.
[0003] Most of the current molded sheets have the defects of poor impact strength, and in the molding, strength and processing of some injection molding and rotational molding equipment, there are phenomena of brittleness, cracking and gaps. Therefore, there are two common production processes for existing acrylic sheets: casting method and extrusion method.
[0004] The casting method is to mix methyl methacrylate (MMA) monomer with other reactants to form a slurry, then inject it into the mold, and achieve polymerization through subsequent heating treatment. This method mainly uses a frame-shaped mold, which is mainly composed of two upper and lower plates. The two plates sandwich the molding materials of the acrylic plate in the middle, and then hang them in a warm water pool for a water bath. After several hours, they are lifted out or moved into warm water pools of different temperatures to wait for the acrylic plate materials in the mold to polymerize and form a solid acrylic plate. This method is mainly characterized by simple operation and low equipment requirements.
[0005] The extrusion method refers to dissolving MMA monomer and other raw materials at high temperature, polymerizing at low temperature to form a suspension, and then forming it through an extruder. The extrusion method can achieve large-scale and large-scale production. However, due to the small molecular weight of PMMA polymerization, its mechanical properties, heat resistance, and solvent resistance are poor, which cannot meet the use requirements of some occasions.
[0006] PMMA has the advantages of light weight, low price, and easy molding. However, acrylic sheets made by common preparation methods in the current market have the disadvantages of limited strength and poor high temperature resistance in actual use. In order to overcome this defect, the existing product production process also adopts a modification method to achieve breakthroughs in mechanical properties and temperature resistance of acrylic sheets. However, when MMA monomers are polymerized to form PMMA polymers, they are prone to prepolymerization. It is difficult to produce qualified acrylic sheets by ordinary casting or extrusion methods. Summary of the invention
[0007] In order to overcome the above problems, the present application provides a high-strength acrylic sheet and a preparation method thereof. The provided high-strength acrylic sheet formula system can be applied to an easy-to-operate casting method, and the obtained acrylic sheet has the advantages of high strength and high temperature resistance.
[0008] In the first aspect, the present application provides a high-strength acrylic plate, which adopts the following technical solution:
[0009] A high-strength acrylic plate comprises the following components in parts by weight: 80-100 parts of methyl methacrylate, 6-8 parts of ethyl acrylate, 2.5-5 parts of graphene oxide, 0.3-0.5 parts of initiator, 8-10 parts of filler, 3-5 parts of flame retardant and 0.5-1 part of antioxidant.
[0010] By adopting the above technical scheme, ethyl acrylate and methyl methacrylate have similar structures. By adding ethyl acrylate, methyl methacrylate can be copolymerized to improve the mechanical properties and high temperature resistance of acrylic sheet. Moreover, the copolymerization of the two has low requirements on production conditions and can be applied to conventional casting method for production and preparation. Since ethyl acrylate has self-lubricating properties, it is not necessary to add release agents such as stearic acid to the formula system, thereby avoiding the influence of release agents and lubricants on the performance of molded products.
[0011] Graphene has the advantages of large specific surface area, high mechanical strength, excellent electrical and thermal conductivity, etc., and is often used as an ideal filler for polymer modification. Graphene oxide is a derivative of graphene, which is prepared by oxidizing graphene. It is rich in a large number of oxygen-containing functional groups and retains the excellent properties of graphene in many aspects. This application adds oxidized graphene, which has stronger chemical modifiability and can be more easily compounded with polymethyl methacrylate, thereby improving the mechanical and thermal properties of acrylic sheets.
[0012] Preferably, 0.1-0.3 parts by weight of metal chloride is also added to the high-strength acrylic board formula.
[0013] By adopting the above technical solution, the amount of graphene oxide added to the matrix resin is limited, and its performance improvement on the matrix resin is limited. By adding metal chloride, the interaction between graphene oxide and the matrix resin can be enhanced, so the mechanical properties of the acrylic sheet can be greatly improved. At the same time, heat is more easily transferred from the molecular chain to the graphene oxide, and the thermal stability of the acrylic sheet has also been improved. After testing, it can be proved that the addition of metal chloride can increase the tensile strength of the acrylic sheet by at least 30% and the softening point by at least 25%.
[0014] Preferably, the metal chloride is cupric chloride or ferric chloride.
[0015] By adopting the above technical scheme, cupric chloride and ferric chloride contain divalent cupric ions and trivalent iron ions. The coordination energy of the divalent cupric ions and trivalent iron ions is relatively strong, and they can form coordination bonds with the coordinating atoms on the graphene oxide sheets or polymers, thereby correspondingly improving the interaction force between the graphene oxide and the matrix resin. At the same time, the strong coordination effect of the divalent cupric ions and trivalent iron ions can stably insert between the graphene oxide sheets, effectively preventing the agglomeration of graphene oxide, improving the dispersibility of graphene oxide in the matrix resin, and correspondingly improving the final mechanical properties of the product.
[0016] Preferably, the initiator is selected from dibenzoyl peroxide and azobisisobutyronitrile.
[0017] Preferably, the filler is selected from one of nano-silicon dioxide and kaolin.
[0018] By adopting the above technical solution, fillers are used as additives to improve the dimensional stability and mechanical properties of the acrylic sheet after molding. This is determined by the dimensional stability of the fillers themselves. In the filled polymer, the movement of the molecular chains in the polymer interface area is restricted, which increases the glass transition temperature, increases the heat deformation temperature, reduces the shrinkage rate, and increases the elastic modulus, hardness, stiffness, and impact strength.
[0019] Preferably, the flame retardant is a mixture of a phosphorus nitrogen flame retardant and an oxaphosphaphenanthrene flame retardant in a mass ratio of 1:(0.5-1). The phosphorus nitrogen flame retardant is preferably HF-900A, and the oxaphosphaphenanthrene flame retardant is preferably 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide.
[0020] By adopting the above technical solution, the phosphorus-nitrogen flame retardant contains nitrogen and phosphorus elements, does not contain halogen, and does not need antimony trioxide as a synergist. The phosphorus-nitrogen flame retardant has the characteristics of being halogen-free, low smoke, low toxicity, and high efficiency. When this flame-retardant polymer is heated, a uniform carbon foam layer can be generated on the surface. It plays the role of heat insulation, oxygen isolation, smoke suppression, and preventing droplets, so it has good flame retardant properties.
[0021] 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide has a high phosphorus content, good heat resistance and chemical stability, is not easy to hydrolyze, not easy to volatilize, has good compatibility with polymers, and is not easy to precipitate. In this application, the oxaphosphaphenanthrene flame retardant is compounded with the phosphorus nitrogen flame retardant, and its flame retardant effect is more significant.
[0022] Preferably, the antioxidant is selected from one or more combinations of antioxidant 1010, antioxidant 1024, and antioxidant 1076.
[0023] By adopting the above technical solution and adding antioxidants, the antioxidant performance and yellowing resistance of the product can be further improved.
[0024] In a second aspect, the present application provides a method for preparing a high-strength acrylic sheet, using the following technical solution:
[0025] A method for preparing a high-strength acrylic plate specifically comprises the following preparation steps:
[0026] S1, mixing methyl methacrylate, ethyl acrylate, graphene oxide, and an initiator and heating them to obtain a copolymer;
[0027] S2, adding filler, flame retardant and antioxidant to the copolymer, mixing evenly to obtain a mixture;
[0028] S3, pouring the mixture into a mold, heat-insulating and curing, cooling, and demolding to obtain the high-strength acrylic sheet. By adopting the above-mentioned technical solution, the present application adopts a casting method to prepare the acrylic sheet. This method is efficient and simple and can be mass-produced. The prepared acrylic sheet has excellent mechanical properties and strong high temperature resistance.
[0029] In summary, this application has the following beneficial effects:
[0030] (1) The present invention improves the mechanical properties and high temperature resistance of acrylic sheets by adding ethyl acrylate monomers and methyl methacrylate monomers for copolymerization, and reduces the requirements for production methods and production equipment during copolymerization. The conventional casting method can be used for production. At the same time, the self-lubricating property of ethyl acrylate is fully utilized, and there is no need to use lubricants such as stearic acid for demolding, thereby further improving the mechanical properties of the finished product.
[0031] (2) The present application adds graphene oxide, which has stronger chemical modifiability and can be more easily compounded with polymethyl methacrylate, thereby improving the mechanical and thermal properties of the acrylic sheet;
[0032] (3) The present application further breaks through the performance improvement of graphene oxide on acrylic sheet by adding metal chloride, which is coordinated and complexed with graphene oxide. After testing, it can be proved that the addition of metal chloride can increase the tensile strength of acrylic sheet by at least 30% and the softening point by at least 25%. DETAILED DESCRIPTION
[0033] The present application is further described in detail below with reference to the embodiments.
[0034] The sources of some raw materials used in the examples and comparative examples of the present application are as follows, and other raw materials without specified sources are purchased from ordinary markets:
[0035] Methyl methacrylate and ethyl acrylate were purchased from Dongguan Xinyang Chemical Co., Ltd.;
[0036] Nano-silicon dioxide was purchased from Beijing Dekedaojin Technology Co., Ltd., model DK-SiO2-30, with an average of 30 nm.
[0037] Example
[0038] Example 1
[0039] A high-strength acrylic sheet, the specific preparation steps are as follows:
[0040] S1, 80 kg of methyl methacrylate, 6 kg of ethyl acrylate, 2.5 kg of graphene oxide, and 0.3 kg of initiator are added to a reactor, stirred and mixed for 10 min, and heated at 80° C. for 30 min to obtain a copolymer;
[0041] S2, adding 8 kg of filler, 3 kg of flame retardant and 0.5 kg of antioxidant to the copolymer, mixing and stirring for 10 minutes to obtain a mixture; S3, pouring the mixture into a mold, heat-curing at 60° C. for 2 hours, cooling to room temperature 25° C., demolding, and obtaining the high-strength acrylic sheet.
[0042] In this embodiment, the thickness of the graphene oxide layer is 2-3 nm and the diameter is 1-2 μm; the initiator is azobisisobutyronitrile; the filler is nano-silicon dioxide; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:0.5; the antioxidant is antioxidant 1010.
[0043] Example 2
[0044] S1, 90 kg of methyl methacrylate, 7 kg of ethyl acrylate, 3.5 kg of graphene oxide, and 0.4 kg of initiator are added to a reactor, stirred and mixed for 15 min, and heated at 80° C. for 35 min to obtain a copolymer;
[0045] S2, adding 9 kg of filler, 4 kg of flame retardant and 0.8 kg of antioxidant to the copolymer, mixing and stirring for 15 minutes to obtain a mixture; S3, pouring the mixture into a mold, heat-curing at 60° C. for 2.5 hours, cooling to room temperature of 25° C., demolding, and obtaining the high-strength acrylic sheet.
[0046] In this embodiment, the thickness of the graphene oxide layer is 2-3 nm and the diameter is 1-2 μm; the initiator is azobisisobutyronitrile; the filler is nano-silicon dioxide; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:0.5; the antioxidant is antioxidant 1010.
[0047] Example 3
[0048] S1, adding 100 kg of methyl methacrylate, 8 kg of ethyl acrylate, 5 kg of graphene oxide, and 0.5 kg of initiator into a reactor, stirring and mixing for 20 min, and heating at 80° C. for 40 min to obtain a copolymer;
[0049] S2, adding 10kg of filler, 5kg of flame retardant and 1kg of antioxidant to the copolymer, mixing and stirring for 20min to obtain a mixture; S3, pouring the mixture into a mold, heat-curing at 60°C for 3h, cooling to room temperature 25°C, demolding, and obtaining the high-strength acrylic sheet.
[0050] In this embodiment, the thickness of the graphene oxide layer is 2-3 nm and the diameter is 1-2 μm; the initiator is azobisisobutyronitrile; the filler is nano-silicon dioxide; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:0.5; the antioxidant is antioxidant 1010.
[0051] Example 4
[0052] A high-strength acrylic sheet, the specific preparation steps are as follows:
[0053] S1, 80 kg of methyl methacrylate, 6 kg of ethyl acrylate, 2.5 kg of graphene oxide, and 0.3 kg of initiator are added to a reactor, stirred and mixed for 10 min, and heated at 80° C. for 30 min to obtain a copolymer;
[0054] S2, adding 8 kg of filler, 3 kg of flame retardant and 0.5 kg of antioxidant to the copolymer, mixing and stirring for 10 minutes to obtain a mixture; S3, pouring the mixture into a mold, heat-curing at 60° C. for 2 hours, cooling to room temperature 25° C., demolding, and obtaining the high-strength acrylic sheet.
[0055] In this embodiment, the thickness of the graphene oxide layer is 2-3 nm and the diameter is 1-2 μm; the initiator is dibenzoyl peroxide; the filler is kaolin; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:0.8; the antioxidant is antioxidant 1024.
[0056] Example 5
[0057] A high-strength acrylic sheet, the specific preparation steps are as follows:
[0058] S1, 80 kg of methyl methacrylate, 6 kg of ethyl acrylate, 2.5 kg of graphene oxide, and 0.3 kg of initiator are added to a reactor, stirred and mixed for 10 min, and heated at 80° C. for 30 min to obtain a copolymer;
[0059] S2, adding 8 kg of filler, 3 kg of flame retardant and 0.5 kg of antioxidant to the copolymer, mixing and stirring for 10 minutes to obtain a mixture; S3, pouring the mixture into a mold, heat-curing at 60° C. for 2 hours, cooling to room temperature 25° C., demolding, and obtaining the high-strength acrylic sheet.
[0060] In this embodiment, the thickness of the graphene oxide layer is 2-3nm and the diameter is 1-2μm; the initiator is azobisisobutyronitrile; the filler is nano-silicon dioxide; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:1; the antioxidant is antioxidant 1076.
[0061] Example 6
[0062] A high-strength acrylic sheet, the specific preparation steps are as follows:
[0063] S1, 80 kg of methyl methacrylate, 6 kg of ethyl acrylate, 2.5 kg of graphene oxide, and 0.3 kg of initiator are added to a reactor, stirred and mixed for 10 min, and heated at 80° C. for 30 min to obtain a copolymer;
[0064] S2, adding 0.1 kg of copper chloride, 8 kg of filler, 3 kg of flame retardant, and 0.5 kg of antioxidant to the copolymer, mixing and stirring for 10 minutes to obtain a mixture;
[0065] S3, pouring the mixture into a mold, curing at 60°C for 2 hours, cooling to room temperature 25°C, and demoulding to obtain the high-strength acrylic plate.
[0066] In this embodiment, the thickness of the graphene oxide layer is 2-3 nm and the diameter is 1-2 μm; the initiator is azobisisobutyronitrile; the filler is nano-silicon dioxide; the flame retardant is a mixture of HF-900A phosphorus nitrogen flame retardant and 10-(2,5-dihydroxyphenyl)-10-hydrogen-9-oxa-10-phosphaphenanthrene 10-oxide in a mass ratio of 1:0.5; the antioxidant is antioxidant 1010.
[0067] Example 7
[0068] A high-strength acrylic plate, which is different from Example 6 in that the amount of cupric chloride used is increased from 0.1 kg to 0.2 kg.
[0069] Example 8
[0070] A high-strength acrylic plate, which is different from Example 6 in that the amount of cupric chloride used is increased from 0.1 kg to 0.3 kg.
[0071] Example 9
[0072] A high-strength acrylic plate, which is different from Example 6 in that ferric chloride is used instead of cupric chloride, and the usage amount is 0.1 kg.
[0073] Comparative Example
[0074] Comparative Example 1
[0075] An acrylic plate, which is different from Example 1 in that butyl acrylate is used instead of ethyl acrylate.
[0076] Comparative Example 2
[0077] An acrylic plate, which is different from Example 1 in that ethyl acrylate is not added.
[0078] Comparative Example 3
[0079] An acrylic plate, which is different from Example 1 in that the amount of graphene oxide used is adjusted from 2.5 kg to 2 kg.
[0080] Comparative Example 4
[0081] An acrylic plate, which is different from Example 1 in that no graphene oxide is added.
[0082] Performance testing
[0083] The acrylic sheets prepared in the above-mentioned embodiments and comparative examples were made into standard sample sheets for performance testing, and the test results are recorded in the following table.
[0084] The tensile strength, impact strength, softening point and heating dimensional change are all based on GB / T 7134-2008 "Casting Industrial Organic Glass Sheet"; the flame retardant performance is based on UL94-2013.
[0085] Standard requirements:
[0086] Tensile strength ≥70MPa;
[0087] Impact strength ≥17KJ·m 2 ;
[0088] Softening point ≥100℃;
[0089] Heating shrinkage ≤2.5%.
[0090] Performance Test Results
[0091] It can be seen from the above test results that the acrylic sheets prepared in Examples 1-9 have mechanical properties and high temperature resistance far exceeding the standard requirements, and the flame retardant grade reaches UL94V-0, showing excellent flame retardant properties.
[0092] Comparing the test results of Example 1 and Comparative Examples 1-4, it can be seen that in Comparative Example 2, no ethyl acrylate monomer was added for copolymerization, and the prepared acrylic sheet was the most basic colorless acrylic sheet, and its strength and softening point were worse than those of Example 1; in Comparative Example 4, no graphene oxide was added, and the prepared acrylic sheet had greatly reduced tensile strength, impact strength, softening point and heating shrinkage performance, indicating that graphene oxide, as a filler, was added to PMMA polymer, which can greatly improve the mechanical properties and high temperature resistance of the acrylic sheet.
[0093] By comparing the test results of Example 1 and Example 6, it can be seen that after adding metal chloride to Example 1 containing graphene oxide, the mechanical properties and high temperature resistance have a significant growth breakthrough, among which the tensile strength and impact strength are increased by more than 30%, and the softening point is increased by more than 25%.
[0094] Comparing the test results of Example 6 and Example 9, it can be seen that Example 6 contains cupric chloride and Example 9 contains ferric chloride, and the performance test results of Example 9 are better than those of Example 6, indicating that using ferric chloride as a metal chloride to compound with graphene oxide is the best choice.
[0095] In summary, the present application adopts ethyl acrylate as the second monomer to copolymerize with methacrylate and adopts the casting method to prepare the acrylic sheet, and the mechanical properties and high temperature resistance of the obtained acrylic sheet are better than those of ordinary acrylic sheets. Moreover, on the basis of the above formula, the introduction of graphene oxide as a filler and the addition of metal chloride for compounding can greatly improve the various properties of the acrylic sheet.
[0096] The above is only the preferred implementation of the present application. The protection scope of the present application is not limited to the above embodiments. All technical solutions under the concept of the present application belong to the protection scope of the present application. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present application should also be regarded as the protection scope of the present application.
Claims
1. A high-strength acrylic sheet, characterized in that: The invention comprises the following components in parts by weight: 80-100 parts of methyl methacrylate, 6-8 parts of ethyl acrylate, 2.5-5 parts of graphene oxide, 0.3-0.5 parts of initiator, 8-10 parts of filler, 3-5 parts of flame retardant, 0.5-1 parts of antioxidant and 0.1-0.3 parts of metal chloride; The metal chloride is selected from cupric chloride and ferric chloride.
2. The high-strength acrylic sheet according to claim 1, characterized in that: The initiator is selected from one of dibenzoyl peroxide and azobisisobutyronitrile.
3. The high-strength acrylic sheet according to claim 1, characterized in that: The filler is selected from one of nano silicon dioxide and kaolin.
4. The high-strength acrylic sheet according to claim 1, characterized in that: The flame retardant is a mixture of a phosphorus nitrogen flame retardant and an oxaphosphaphenanthrene flame retardant in a mass ratio of 1:(0.5-1).
5. The high-strength acrylic sheet according to claim 1, characterized in that: The antioxidant is selected from one or more combinations of antioxidant 1010, antioxidant 1024, and antioxidant 1076.
6. The method for preparing the high-strength acrylic sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, mixing methyl methacrylate, ethyl acrylate, graphene oxide, and an initiator and heating them to obtain a copolymer; S2, adding metal chloride, filler, flame retardant and antioxidant to the copolymer, mixing evenly to obtain a mixture; S3, pouring the mixture into a mold, curing by heat preservation, cooling, and demolding to obtain the high-strength acrylic plate.
Citation Information
Patent Citations
Nanomaterial-reinforced resins and related materials
US20110245378A1
Craze resistant transparent sheet
US5549941A